Melatonin combined with static magnetic field acquire better protective effects on bone mass and bone strength in osteoporosis induced by ovariectomy in rats - Hanli Lu; Nannan Gan; Jun Du; Tianle Xue; Desheng Hou; Cheng Lu (Annals of Medicine)
Objective This research aimed to examine the possible impacts of Melatonin (Mel) combined with static magnetic field (SMF) on bone mass and strength in rats with osteoporosis induced by bilateral ovary removal.Methods Following bilateral ovariectomy, the female ovariectomized (OVX) rats were systematically allocated into four distinct experimental groups: (1) OVX (control group), (2) OVX+melatonin (OVX+Mel), (3) OVX+magnetostatic field (OVX+SMF), and (4) OVX+melatonin/magnetostatic field (OVX+Mel/SMF). The intervention protocol consisted of daily administration of melatonin (30 mg/kg/day), exposure to a static magnetic field (50 ± 4 µT), or a combination of both treatments for a duration of 12 weeks. Upon completion of the treatment period, comprehensive biological samples were collected, including blood specimens and bilateral femurs, for subsequent multi-modal analyses. These analyses encompassed Micro-CT imaging for bone microarchitecture evaluation, histological examination for tissue morphology, biomechanical testing for bone strength assessment, serum cytokine profiling, oxidative stress marker quantification, bone metabolic marker analysis, and RT-PCR for gene expression evaluation.Results Micro-CT evaluation indicated that OVX rats treated with Mel and SMF had significantly higher BMD, BMC BV/TV, Tb. N, and Tb. Th values, along with lower Tb. Sp than the OVX+SMF and OVX+Mel groups (all p < 0.05). Histological analysis showed that the combination of Mel and SMF notably improved trabecular quality while increasing MAR, OC, and SOD2 expression, and reducing TRAP and TNF-α levels compared to the OVX+SMF and OVX+Mel groups (all p < 0.05). Biomechanical tests demonstrated that combined treatment enhanced maximum load, stiffness, energy absorption, ultimate stress, toughness, and elastic modulus in comparison to the OVX+SMF and OVX+Mel groups (all p < 0.05). RT-PCR results revealed a significant increase in SIRT1 and OPG expression while inhibiting RANKL and SOST compared to the OVX+SMF and OVX+Mel groups (all p < 0.05). Serum tests found that this combination treatment significantly reduced levels of P1NP, CTX-1, MDA, TNF-α, and IL-6 while increasing SOD expression relative to the OVX+SMF and OVX+Mel groups (all p < 0.05).Conclusion Our results indicate that Mel combined with SMF has the potential to be an effective method for preventing bone loss and maintaining bone strength in postmenopausal osteoporosis.